(untitled) (Bangladesh Journal of Child Health, 2018)
Background: There are several forms of pulmonary manifestations in Paediatric Rheumatic Diseases (PRDs), not only by the disease itself, but also by infections and toxicity of medications used for treatment. Objectives: To evaluate the pulmonary manifestations and to identify their pattern in PRDs including Systemic Lupus Erythematosus (SLE), Juvenile Idiopathic Arthritis (JIA), Systemic Sclerosis (SSc), Juvenile Dermatomyositis (JDM) and Polyarteritis Nodosa (PAN) patients. Methods: It was a cross-sectional analytical study. PRDs with pulmonary problems who attended the Paediatric Rheumatololgy follow up clinic of BSMMU from January 2010 to December 2014 were enrolled in this study. All patients having PRDS with pulmonary symptoms were investigated by chest x-ray. High regulation CT scan of Chest (HRCT) and pulmonary function tests (PFTs) were done in some of the feasible cases. Results: Total 20 cases were identified as paediatric rheumatic diseases with pulmonary manifestations. Out of them 8 patients were diagnosed as SLE, 6 patients as SSc, 4 patients as JIA, and 2 patients as JDM and PAN respectively. Mean age of the patients were 8.5 years. Fever (86.8%), prolonged cough (65%), dyspnoea (29%) and chest pain (3%) were the common pulmonary features. Pneumonitis (35%), pleural effusion (29.3%), consolidation (23.5%) were important radiological findings. Chest CT were done in 5 patients and features of brochiectasis (75%), thickening (25%), pleural effusion (50%) and pneumonitis (50%) were found. The higher rate of pulmonary involvement was found in Ssc (100%). Spirometric analysis were done in only 7 patients and found restrictive pattern of defect and most of them were SSc. Conclusion: Pulmonary manifestations in PRDs were not uncommon. SLE, JIA and SSc were the predominant PRDs who had pulmonary manifestations obsevered in this study. So timely intervention of this issue could minimize morbidity and mortality of these diseases in the long run. Bangladesh J Child Health 2017; VOL 41 (2) :96-100